Dynamic responses and stability analysis of a large-scale slope deposit under non-uniform seismic input - Chong Shi; Tianjiao Qiao; Dawei Xue; Su Wu; Cong Zhang (Geoenvironmental Disasters)
Abstract Background Slope deposits, widely distributed in Southwest China, may experience considerable deformation under earthquakes, posing a risk of large-scale landslides that could result in property damage and threaten human safety. This paper aims to look into the dynamic reactions and stability of a three-dimensional slope deposit under non-uniform seismic input. Method This work formulates an analytical solution for non-uniform seismic input problems tailored to slopes. Subsequently, numerical simulations are conducted using the finite difference method to detect the characteristics of dynamic responses in the slip zone and landslide surface of a slope model, which is set up by referencing a typical slope deposit in Southwest China. The impacts of key factors on slope stability are analyzed using a novel perturbation method designed for three-dimensional slope deposits with complex geometry. Results The analysis of dynamic responses reveals that the acceleration magnification factors are smallest for the lower boundary of the slip zone and largest for the landslide surface. Maximum accelerations peak at the midpoint of the slope model and stabilize at certain values with increasing elevation. The difference in peak acceleration values for the landslide surface and the slip zone decreases rapidly and gradually approaches zero, as the landslide body thickness increases. Slope stability analysis indicates that non-uniform and uniform inputs do not exhibit significant differences in terms of the extremum values of computed safety factors, but the former indicates a much lower average safety factor as time goes on. The increase in epicentral distance and earthquake intensity leads to an increase, with a decreasing rate, in overall safety factors. As time progresses, all computed safety factors show diminished fluctuation and approach specific values. Conclusions The study reported here underscores the significance of incorporating non-uniform seismic input when assessing the stability of deposit slopes during earthquakes. The integration of analytical solutions for non-uniform input, continuum-based numerical simulations, and limit equilibrium concept can form a robust strategy for studying earthquake-induced landslides of three-dimensional deposit slopes with complex geometry.